Impact of stroke mechanism in acute basilar occlusion with reperfusion therapy - Lee, Woo‐Jin (Ann Clin Transl Neurol, 2018)
OBJECTIVE: We aimed to evaluate the impact of underlying mechanism of basilar artery (BA) occlusion on the outcomes after endovascular therapy (EVT) for reperfusion and the outcome factors associated with each mechanism, and to identify radiologic parameters enabling to distinguish the underlying mechanism. METHODS: From a registry database, 194 consecutive patients with acute BA occlusion who underwent EVT were analyzed. Stroke mechanism, classified into in situ atherosclerotic thrombosis (ISAT) and embolism, clot sign location profiles in pre‐angiography magnetic resonance image (MRI), parameters of angiography and EVT, and reperfusion were assessed. Poor outcome was defined as a modified Rankin‐Scale score at 90 days of 3–6. RESULTS: The mean age was 68.8±11.8 years (range 21–92 years) and seventy‐eight (40.2%) were female patients. 102 (52.6%) patients were classified into an embolism mechanism and 92 (47.4%) into an ISAT mechanism. Overall, ISAT mechanism compared with embolism was significantly associated with poor outcomes (P = 0.002), along with the NIHSS scores, reperfusion status, and collateral status. In the embolism group, reperfusion (P = 0.001), NIHSS scores (P < 0.001), and onset‐to‐treatment time (P = 0.030) were significant outcome factors. However, in the ISAT group, baseline collateral status (P = 0.001) and NIHSS scores (P < 0.001) were significant outcome factors. A clot sign at the distal BA segment on pre‐angiography MRI was strongly associated with embolism mechanism (P < 0.001). INTERPRETATION: Stroke mechanism has a major influence on outcomes, and outcome predictors differ according to the underlying mechanism in acute BA occlusion with EVT. Clot sign profile on pre‐angiography MRI might be useful to determine the underlying mechanism.